Synthesis of BiOI-TiO2 Composite Nanoparticles by Microemulsion Method and Study on Their Photocatalytic Activities - Yunfang Chen; Xiaoxin Xu; Jianzhang Fang; Guangying Zhou; Zhang Liu; Shuxing Wu; Weicheng Xu; Jinhui Chu; Ximiao Zhu (The Scientific World Journal)
This study was conducted to synthesize a series of nanosized BiOI-TiO2 catalysts to photodegrade Bisphenol A solution. The BiOI-TiO2 nanoparticles were synthesized in the reverse microemulsions, consisting of cyclohexane, Triton X-100, n-hexanol, and aqueous salt solutions. The synthesized particles were characterized by X-ray diffraction (XRD), Brunauer-Emmett-Teller (BET) surface analyzer, Fourier transform-infrared spectroscopy (FT-IR), ultraviolet-visible light (UV-Vis) absorption spectra and transmission electron microscope (TEM). The photodegradation of Bisphenol A (BPA) in aqueous suspension under visible light irradiation was investigated to explore the feasibility of using the photocatalytic method to treat BPA wastewater. The effects of different molar ratios of BiOI to TiO2 on the photocatalytic activity were discussed. The experimental results revealed that the photocatalytic effect of the BiOI-TiO2 particles was superior to the commercial P25 TiO2. The BPA degradation could be approached by a pseudo-first-order rate expression. The observed reaction rate constant (kobs) was related to nanoparticles dosage and initial solution pH.